RESPON PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium cepa L) TERHADAP KONSENTRASI AIR KELAPA DAN MEDIA TANAM SECARA VERTIKULTUR - Lokot Ridwan Batubara; Rita Mawarni; Rizky Raka Reyanda Pohan (Jurnal Agrotek Ummat, 2021)
The study was conducted at experimantal field at Faculty of Agriculture, Asahan University, Asahan Regency on October 2020 until December 2020. The study aims to the find out the growth response and production of shallots (Allium cepa L.) to the concentration of coconut water and growth media veticulture. This study used randomized complete block design with two factors: (1) Concentration of coconut water (K) with 3 levels: K1 = 25% (250 ml coconut water + 750 ml water), K2 = 50% (500 ml coconut water + 500 ml water), K3 = 75% (750 ml coconut water + 250 ml water) and (2) growth media (M) with 3 levels: M1 = soil + cow manure (1:1), M2 = soil + cow manure (2:1), M3 = soil + cow manure (3:1). Observation parameters were plant height, number of leave, number of bulbs, bulbs weight. The results showed that coconut water concentration had a significant effect on the number of tubers per clump and tuber wet weight, but had no significant effect on observations. plant height and number of leaves, the best treatment at K3 = 75% (750 ml coconut water + 250 ml water). The planting medium did not significantly affect the observations of plant height, number of leaves, number of tubers per clump and wet weight of tubers. The interaction between the concentration of coconut water and growing media did not have a significant effect on all observed variables.